Design and structural analysis of an inflatable coated fabric manipulation arm. (June 2019) - Liu, Yu; Zhang, Daxu; Hu, Jianhui; Chen, Wujun; Gao, Chengjun; Qiu, Zhenyu
Abstract: This paper presents the structural behaviour of a novel inflatable manipulation arm, which consists of inflatable coated fabric tubes and bellows-type joints. In order to minimise the actuation moment, a rotational joint with creases, analogous to a spacesuit elbow, has been introduced. The biaxial tensile and shear tests have been carried out to evaluate the elastic constants of the PVC-coated polyester fabric membranes of the inflatable arm. Finite element analysis has been carried out to predict the mechanical behaviour of the inflated arm structure. Effects of the internal pressure on the arm deflection, and influence of crease geometric parameters, e.g. number, width and depth on the rotation performance are evaluated. A prototype of the inflatable arm has been developed to perform an experimental investigation on its rotational behaviour. Good correlations have been found between the predictions and the experimental results. The current work on a representative single-joint inflatable arm unit provides the rationale and knowledge to develop long range multi-joint manipulators. Highlights: A manipulation arm structure integrated by inflatable membrane tubes and creased joints is proposed. A finite element model was created to predict the structural behaviour of a representative single-joint unit. A prototype was developed to perform experimental studies and validate predictions. Parametric studies on the number, depth and width of creases were carried out. The rotational and flexural behaviour of the manipulation arm was discussed.